The efficacy of traditional songs in the control of deviant behaviour of incest among Yoruba people of South-western Nigeria. (2022)
Incest is a cultural term that describes sexual contact between members that are closely related, especially between members of a nuclear family, that is, between parents and children or between siblings. The alarming rate of incest in our societies in the recent times calls for an urgent attention as it has brought a dirty blow on family stability and societal structure. Existing literature on incest have focused more on the modem approaches to deal with culprits of incest like making an arrest and prosecution by the police and other security agencies of culprits while little attention is paid to how traditional songs were used in time past to deal with offenders thereby bringing the menace to a barest minimum and restoring sanity into the society. The incessant cases of incest in the society makes it imperative to explore one of the mechanisms that was effectively used in the pre-colonial time to restore social order. Traditional songs were copiously intoned to address the menace of incest which led to the considerable peace experienced in the past by the Yoruba people. Oral tradition and written records that are relevant to the subject matter were made use of in this study. We observed through our findings that traditional songs were more effective in the pre-colonial period in controlling deviant behaviour of incest and can also play a complimentary role in the rejuvenation of social order in Yoruba society today, if properly and systematically integrated.